Functional Metabolic Mapping Reveals Highly Active Branched-Chain Amino Acid Metabolism in Human Astrocytes, Which Is Impaired in iPSC-Derived Astrocytes in Alzheimer's Disease - Salcedo, Claudia; Andersen, Jens V.; Vinten, Kasper Tore; Pinborg, Lars H.; Waagepetersen, Helle S.; Freude, Kristine K.; Aldana, Blanca I. (Frontiers in Aging Neuroscience, 2021)
The branched-chain amino acids (BCAAs) leucine, isoleucine and valine are important nitrogen donors for synthesis of glutamate, the main excitatory neurotransmitter in the brain. The glutamate carbon skeleton originates from the tricarboxylic acid (TCA) cycle intermediate α-ketoglutarate whilst the amino group is derived from nitrogen donors such as the BCAAs. Disturbances in neurotransmitter homeostasis, mainly of glutamate, are strongly implicated in the pathophysiology of Alzheimer´s disease (AD). The divergent BCAA metabolism in different cell types of the human brain is poorly understood and thus is the involvement of astrocytic and neuronal BCAA metabolism in AD. The aim of this study is to provide the first functional characterization of BCAA metabolism in human brain tissue and to investigate BCAA metabolism in AD pathophysiology using astrocytes and neurons derived from human induced pluripotent stem cells (hiPSC). Mapping of BCAA metabolism was performed using mass spectrometry and enriched [15N] and [13C] isotopes of leucine, isoleucine and valine in surgically resected cerebral cortical tissue from human brain, acutely isolated cerebral cortical slices from mouse and hiPSC-derived brain cells. The investigated hiPSC lines carry mutations in either amyloid precursor protein (APP) or presenilin-1 (PSEN-1). Here, we reveal that both human astrocytes of acutely isolated cerebral cortical slices and hiPSC derived astrocytes were capable of oxidatively metabolizing the carbon skeleton of BCAAs, particularly to support glutamine synthesis. Interestingly, hiPSC-derived astrocytes with APP and PSEN-1 mutations exhibited decreased amino acid synthesis of glutamate, glutamine and aspartate derived from leucine metabolism. These results clearly demonstrate that there is an active BCAA metabolism in human astrocytes and that leucine metabolism is selectively impaired in astrocytes derived from the hiPSC-models of AD. This impairment in astrocytic BCAA metabolism may contribute to neurotransmitter and energetic imbalances of the AD brain.